Grammatical Challenges in English Writing among First-Year University Students - Abbas, M. Fadhly Farhy; Fathira, Vina; Masbiran, Gunaldi (ENGLISH JOURNAL OF INDRAGIRI, 2026)
Grammar is a crucial component of English writing, yet many first-year university students face difficulties in applying it correctly. This study aims to explore the grammatical challenges of first-year university students in English writing, including their difficulties, strategies, and perceptions. This qualitative study involved 10 first-year university students enrolled in an introductory English course at a university in Pekanbaru, providing insights into their grammatical challenges, strategies, and perceptions in English writing. Data were collected through interviews. The responses were analyzed thematically and illustrated using direct quotations. The findings revealed that students frequently struggle with tenses, subject–verb agreement, prepositions, and sentence structure. Writing frequency varied, with some students practicing regularly while others wrote only when assigned. Strategies to improve grammar included reading example sentences, using applications and books, asking peers or teachers for feedback, and self-correction. Students acknowledged that understanding grammar is important for clarity, effective communication, and academic success. The study highlights the need for structured grammar instruction, regular writing practice, and effective feedback. Providing reliable resources and emphasizing common error patterns can help students overcome grammatical challenges and enhance their writing skills. It is recommended that educators provide targeted grammar lessons focusing on common errors, integrate digital tools to support autonomous learning, and encourage consistent writing practice to help students enhance their grammar skills and overall writing proficiency.